2013
DOI: 10.3109/14397595.2013.843748
|View full text |Cite
|
Sign up to set email alerts
|

Increased serum concentration of BAFF/APRIL and IgA2 subclass in patients with mixed connective tissue disease complicated by interstitial lung disease

Abstract: B cell activating factor (BAFF) and a proliferation-inducing ligand (APRIL) are known to be crucial for B cell maturation and survival, and increased expression of these factors in various autoimmune diseases has been reported. Human B cells produce two IgA subclasses: IgA1 and IgA2, the latter being abundant in the distal intestine, saliva, colostrum and bronchial fluid. We investigated these parameters in patients with mixed connective tissue disease (MCTD) complicated by interstitial lung disease (ILD+), an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…A series of data have uncovered that BAFF acts as a crucial factor in aggressive B-cell malignancies and various autoimmune diseases, such as SLE, RA and SS [13, 21, 41, 46, 47]. For example, lupus serum contains elevated levels of BAFF [48].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A series of data have uncovered that BAFF acts as a crucial factor in aggressive B-cell malignancies and various autoimmune diseases, such as SLE, RA and SS [13, 21, 41, 46, 47]. For example, lupus serum contains elevated levels of BAFF [48].…”
Section: Discussionmentioning
confidence: 99%
“…High levels of BAFF evoke prolonged lifespan B-cell disorders [49, 50]. The SLE patients suffer from numerous pathogenic autoantibodies released from aggressive B cells, due to excessive BAFF [17, 21, 46]. However, abnormal release or effects of diverse other cytokines have been also documented in SLE patients and animal models both in vitro and in vivo , pointing to association of the autoimmune disease with the dysregulation of complex cytokine networks [47, 51].…”
Section: Discussionmentioning
confidence: 99%
“…Serum BAFF levels are associated with disease activity for these clinical entities. Furthermore, it has been shown the myositis and mixed CTD (MCTD) patients with ILDs have significantly higher BAFF levels than those without ILDs [ 16 , 17 ]. A recent study showed plasma BAFF concentrations are significantly higher in IPF patients than in either COPD patients or control subjects [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…B-cell activating factor of the TNF family is known to be crucial for B cell maturation and survival, and especially increased expression of BAFF in various autoimmune diseases, such as RA, SS and SLE, has recently received more attention [5,12,51]. For example, high levels of BAFF contribute to aggressive or neoplastic B cell disorders [16,17].…”
Section: Discussionmentioning
confidence: 99%
“…For example, high levels of BAFF contribute to aggressive or neoplastic B cell disorders [16,17]. Patients suffer from a great quantity of autoantibodies secreted from aggressive B cells, whose root is excess BAFF [8,12,51]. However, the signaling pathways that can be activated by BAFF are complex and controversial.…”
Section: Discussionmentioning
confidence: 99%